The shift towards CEFR-aligned curriculum in CFS IIUM: a correlational study between SPM 1119 and IIUM English Placement Test - Shuhaimi, Nur Syahirah; Hassanuzin, Salsabilla; Jatin, Norhazwanie (CFS IIUM, 2022)
To ensure the quality of English instruction in Malaysia, all levels of education: primary, secondary, and tertiary, have gradually aligned their curriculum to the Common European Framework of Reference for Languages, or widely known as CEFR. Adapted by more than 60 countries, this ruler serves as a more universal language proficiency barometer, extending its pertinence to other languages as well. Jumping on the bandwagon, the Ministry of Education Malaysia documented the aspiration in the blueprint: English Language Education Reform in Malaysia: The Roadmap 2015-2025. Following the blueprint, Centre for Languages and Pre-University Academic Development, International Islamic University Malaysia (CELPAD IIUM) has aligned its English curriculum with CEFR. Major curriculum review has taken place and revamps have been made in its English courses’ syllabi and assessments. As a matter of course, the revision has affected the conduct of the English Placement Test (EPT) which employed a different standard of measurement system prior to CEFR. This paper seeks to determine the correlation of the results of English Language (SPM 1119) and IIUM English Placement Test (EPT). The study involved new intake CFS IIUM students (N = 2549), the first batch of post-secondary students who went through the CEFR-aligned curriculum. Kendall’s tau-b (τb) correlation coefficient was used to investigate the strength of the association between English SPM and EPT scores. It was found that there was a strong (τb=.357) and significant (p<0.01) correlation between both variates. This indicated those who gained higher grades in SPM 1119 tended to be exempted from English language subjects.